EFFORT TO IMPROVE WRITING SKILLS PARAGRAPH PERSUASIVE THROUGH GRADE VIII STUDENT IMAGE MEDIA SMP NEGERI 3 ALASA TALUMUZOI - Telaumbanua, Minawati (Al'Adzkiya Journal, 2020)
Language is communication tool. One part of teaching writing skills is writing or composing paragraphs. Based on the results of observations by researcher to Indonesia language subject teachers in SMP N 3 Alasa Talumuzoi it was found that some problems in learning to write persuasive paragraphs were still lacking, students’ understanding in arranging words in form a persuasive paragraphs was still lacking, because student were still lacking understand the meaning and way of writing persuasive paragraphs. The research problem is limited to “ Effort to Improve Writing Skill Paragraph Persuasive Through grade SMP N 3 Alasa Talumuzoi 2020/2021. The formulation of this research is how to improve and process image media in improve persuasive paragraph writing skill and the process of class VIII SMP N 3 Alasa Talumuzoi. While the purpose of this study was to describe to improvement of persuasive paragraph writing skills the process of drawing media for class VIII SMP N 3 Talumuzoi. The method used in this study namely classroom action research using image media, which means media that combines the expression of word in pictures. The result of the research in the first cycle with an average student score of 43,92 with a completeness percentage of 11,90 % and the percentage of 88.09 % incompliance indicate that the level of mastery was still lacking. Furthermore in the second cycle with an average student score 80,11 with a completeness percentage of 95,24 % and a percentage of 4, 76 % incompleteness, an increase in the level of mastery showed excellent. The conclusion in this study by applying image media can improve students’ ability to write persuasive paragraph and student are more active in learning and the suggestion in this study are expected to provide input for Indonesian language and literature subject teachers in SMP N 3 Alasa Talumuzoi by applying image media in writing persuasive paragraphs is expected to increase student’ insight in solving a problem.